The environmental aspects of multi-parameter optimization of energy turbines based on life cycle criteria - Klymenko, Vadym (National Technical University "Kharkiv Polytechnic Institute", 2025)
Optimization of the environmental aspects of energy turbines at all stages of their life cycle is an important step in achieving sustainable development and reducing the negative impact on the environment. Emission reduction technologies at energy facilities, particularly for carbon, nitrogen oxides, and sulfur, play a crucial role in ensuring environmental safety. Modern methods of ecological optimization involve the implementation of cutting-edge technologies at all stages of the life cycle of energy turbines. The key aspects of ecological optimization in energy facilities that burn fuel have been studied.
Keywords: environmental aspects; energy turbines; life cycle; multi-parameter optimization; emission reduction